Wastage Pay Smart Bin - Karuppiah, N.; Senthil Kumar, S.; Ravivarman, S.; Joel Joshuva, P.; Prabhu, A.; Arun Kumar, R. (International Journal of Engineering and Technology, 2018)
The separation of waste materials into degradable and non-degradable waste is one of the major issues in our country. As the plastic materials cause major harm to the humans as well as the environment it should be separated and effectively recycled. The non-degradable plastic wastes do not allow the rain water to pass through it thereby decreasing the ground water level. If these wastes are burnt, it emits carbon monoxide which is harmful to the humans. Our project is to encourage the people to dump and segregate the waste materials in their households using smart bins. The separation of the plastic waste is done by using capacitive type proximity sensor and ultrasonic sensor. In order to encourage the people to collect and segregate the waste materials, in large amount, they are rewarded for the amount of waste that they collect and segregate. The amount of waste collected is displayed in the website and in their mobile phones with the amount of reward points earned. The customers redeem their reward points in the shops mentioned in the website.Â Â